2016
DOI: 10.1080/1343943x.2016.1146908
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced root plasticity of two upland NERICA varieties under conditions with contrasting soil depth characteristics

Abstract: To identify differences in root plasticity patterns of two upland New Rice for Africa (NERICA) varieties, NERICA 1 and 4, in response to drought under conditions with contrasting soil profile characteristics, soil moisture gradients were imposed using a sloping bed system with depths ranging 30-65 cm and a line-source sprinkler system with a uniformly shallow soil layer of 20 cm depth. Varietal differences in shoot and root growths were identified only under moderate drought conditions, 11-18% v/v soil moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Similar findings were reported in upland rice under cultivation environments in sub-Saharan Africa (Asch, Dingkuhn, Sow, & Audebert, 2005). We also showed that upland NERICA varieties did not enhance lateral root growth under severe drought conditions, while under mild to moderate drought conditions, approximately −18 to −48 kPa of soil water potential, varietal differences were observed among upland NERICAs in the ability to enhance lateral root growth (Menge et al, 2016). Moreover, Kato and Okami (2010) reported that stomatal behaviour under mild to moderate drought conditions differs depending on the variety.…”
Section: Intensity Of Drought Stresssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported in upland rice under cultivation environments in sub-Saharan Africa (Asch, Dingkuhn, Sow, & Audebert, 2005). We also showed that upland NERICA varieties did not enhance lateral root growth under severe drought conditions, while under mild to moderate drought conditions, approximately −18 to −48 kPa of soil water potential, varietal differences were observed among upland NERICAs in the ability to enhance lateral root growth (Menge et al, 2016). Moreover, Kato and Okami (2010) reported that stomatal behaviour under mild to moderate drought conditions differs depending on the variety.…”
Section: Intensity Of Drought Stresssupporting
confidence: 88%
“…This is consistent with reports by Niones et al (2012) and Suralta et al (2008b), who found genotypic differences in the ability to enhance root system development in response to fluctuating soil moisture conditions. In our previous study, NERICA 1 was found to have a greater ability to enhance lateral root growth than NERICA 4 under moderate drought stress (Menge et al, 2016). The same trend was demonstrated in this study by the fact that NERICA 1 exhibited greater root elongation under fluctuating soil moisture conditions than NERICA 4 (Tables 1 and 5 (Table 5).…”
Section: Varietal Differences In Shoot and Root Growth Under Fluctusupporting
confidence: 88%
“…Previous studies have shown experimental evidences of genotypic variations in root plasticity expressed in response to heterogeneous soil environments for the adaptation of rice plants (Bañoc et al, 2000a;Siopongco et al, 2008;Kano-Nakata et al, 2013;2017;Kameoka et al, 2015;Menge et al, 2016;Niones et al, 2012;Nguyen et al, 2018;Owusu-Nketia et al, 2018;Suralta et al, 2010Suralta et al, , 2016Suralta et al, , 2018Tran et al, 2014). In this study, the CSSLs showed no significant differences in root system development with the recurrent parent under CWL in both experiments.…”
Section: Discussionmentioning
confidence: 50%
“…Digital images were then taken using an image scanner (EPSON Perfection V700 Photo) at 400 dpi resolution. The TRL was analyzed using WinRhizo software (Regent Instruments Inc., Saint-Foy, Canada) (Kameoka et al, 2015;Menge et al, 2016). A pixel threshold value of 175 was set for the root length analysis (Nguyen et al, 2018;Suralta et al, 2018).…”
Section: Shoot and Root Measurementsmentioning
confidence: 99%
See 1 more Smart Citation